Health-associated infections and COVID-19 in Mexico: safety and health rules at work or job biosecurity? - Ruiz Mejia, Ramón; Villeda González, Juan David; Méndez Durán, Antonio (International Journal of Occupational Safety and Health, 2021)
The pandemic caused by COVID-19 has grown exponentially from the first reports from China in December 2019 to November 2020. Cases have been reported in more than 180 countries, totaling more than 61.8 million cases of COVID-19 throughout the world and more than 1.4 million deaths. Health personnel, being exposed to the care of COVID-19 patients with high viral load, have the risk of developing infections associated with health care, their high morbidity and mortality being of multifactorial origin. Given that the term Biosafety and Occupational Biosafety has been used internationally, this term does not have wide acceptance in the scientific community and in the case of Mexico it is not referred to and it is not defined in the Mexican legal framework or current regulations. Far from being handled and understood as an isolated concept, this term should be referred to as multiple concepts, being recommended in the workplace in Mexico not to use it, suggesting referring to the Safety and Health Regulations at Work, whose mandatory application will allow reducing healthcare-associated infections.